2016
DOI: 10.1002/hon.2373
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between venetoclax exposure, rituximab coadministration, and progression‐free survival in patients with relapsed or refractory chronic lymphocytic leukemia: demonstration of synergy

Abstract: Venetoclax is indicated at a dosage of 400 mg daily (QD) for the treatment of patients with chronic lymphocytic leukemia (CLL) with 17p deletion who have received at least 1 prior therapy. Ongoing trials are evaluating venetoclax in combination with CD20 targeting monoclonal antibodies, such as rituximab. The objective of this research was to characterize the relationship between venetoclax exposures and progression-free survival (PFS) and to evaluate the effect of rituximab coadministration on PFS in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…23 An exposure progression-free survival (PFS) analysis demonstrated that higher exposures are likely to increase PFS. 24 With regard to safety, subjects receiving venetoclax doses up to 1200 mg once daily, where the exposures were approximately 2.5-fold higher than those achieved at the approved dose of 400 mg once daily, did not experience dose-limiting toxicities. 6,25,26 Consistently, exposure-safety analyses indicated that higher venetoclax exposures had no effect on QT interval and were not associated with an increase in grade 3 or higher adverse events of neutropenia and infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 An exposure progression-free survival (PFS) analysis demonstrated that higher exposures are likely to increase PFS. 24 With regard to safety, subjects receiving venetoclax doses up to 1200 mg once daily, where the exposures were approximately 2.5-fold higher than those achieved at the approved dose of 400 mg once daily, did not experience dose-limiting toxicities. 6,25,26 Consistently, exposure-safety analyses indicated that higher venetoclax exposures had no effect on QT interval and were not associated with an increase in grade 3 or higher adverse events of neutropenia and infection.…”
Section: Discussionmentioning
confidence: 99%
“…In an exposure–efficacy analysis conducted using data from subjects with CLL (predominantly whites), the rate of objective response was shown to be similar, with a 0.5‐ to 2.0‐fold change in venetoclax exposure from that typically achieved at the 400‐mg once‐daily dosage regimen . An exposure progression‐free survival (PFS) analysis demonstrated that higher exposures are likely to increase PFS . With regard to safety, subjects receiving venetoclax doses up to 1200 mg once daily, where the exposures were approximately 2.5‐fold higher than those achieved at the approved dose of 400 mg once daily, did not experience dose‐limiting toxicities .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, venetoclax was approved by the US FDA for treatment of newly diagnosed AML in adults who are aged 75 years or older or who have comorbidities that preclude use of intensive induction chemotherapy in combination with HMAs or LDAC under accelerated approval pathway. Previous studies have evaluated the venetoclax exposure response relationships in subjects with CLL, non‐Hodgkin's lymphoma, or multiple myeloma . The findings of the analyses reported herein provide the rationale and justification for the dose of venetoclax used in the pivotal, global, randomized, double‐blind, placebo‐controlled phase III study in combination with azacitidine versus azacitidine alone (NCT02993523) and in combination with LDAC vs LDAC alone (NCT03069352), conducted in treatment‐naïve elderly patients with AML who are ineligible for standard induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, higher average venetoclax concentrations (through 1200 mg once daily) were not associated with an increase in adverse events (grade ࣙ3) of neutropenia or infection rates or increases in the QT interval. 28,29 Additionally, venetoclax exposures below those achieved with 400 mg venetoclax may reduce progression-free survival in subjects with R/R CLL, 30 so dose reductions greater than the increases in exposures due to drug-drug interactions could result in decreased efficacy.…”
Section: Discussionmentioning
confidence: 99%